An evaluation of the Science Learner Assisted Program (SLAP) at the University of Limpopo Science Centre, South Africa - Potgieter, M. J.; Potgieter, A.; Ramaila, P. R.; Wildschut, L. (Technium Social Sciences Journal, 2021)
This paper is an evaluation of the Science Learner Assisted Programme (SLAP) at the University of Limpopo Science Centre. The evaluation is intended to be useful for improving the program and informing social action aimed at amending educational problems (related to science education faced by schools in the Limpopo Province (South Africa). The purpose of the evaluation was to evaluate the design of SLAP and how it was being delivered to the target group (Grade 10-12 learners). Data were collected from August to October 2016. Data were collected via documentation review, semi-structured interviews, questionnaires, and observations. Forty-five learners completed the questionnaires. Qualitative and quantitative data analysis techniques were employed during the data analysis process. In terms of program design, the evaluation found that SLAP is aligned with the goals of the University of Limpopo Science Centre. With regard to program delivery, the evaluation found that the program’s major activity is performing experiments. Methods of engaging learners include class discussions, presentations, and group discussions. The methods proved to be effective as the level of participation was high during lessons. Affordability of lessons, the performance of experiments, and information sharing was mentioned as aspects of implementation facilitating the success of the program, while overcrowding, small labs, insufficient resources, and learners being unprepared for lessons were reported as impeding the success of service delivery. Teachers reported that the program was of great assistance to them as they learn to simplify topics and improve their methods of engaging learners in class